School as Narrated Places: Children´s Narratives of School Enjoyment - Eeva Kaisa Hyry-Beihammer; Outi K. Autti (University of Aberdeen, School of Education, 2013)
This article considers school as a place narrated by students. The goal is to understand students’ experiences of their school as a place through the ‘sense of place.’ The empirical data was collected at a small village school in northern Finland during one week of ethnographic observation, which involved interviewing students, collecting students’ writings, and observing teaching. Using content analysis and narrative analysis, three types of narratives were analyzed: One, narratives of relations in place describe students’ experience of their school as a familiar, safe, peaceful place. Two, narratives of action in place emphasize that sense of place is based on places of common action and belonging, for example, in the schoolyard, in the school’s surroundings and environment, on school trips, and during school festivities. Three, narratives of self in place give insights into friendships at a small school. A small school enables close, long-lasting friendships, strengthening the sense of place. Students who switch schools may have difficulties adjusting to tight groups of students; those difficulties may produce feelings of being an outsider. This article also aims to introduce the significance of place in discussions concerning school politics and didactics. An evaluation of the significance of school as a place from the children’s point of view is suggested as a new perspective for discussions and decision-making regarding school closures. This new perspective should focus on how schools as places support children’s growth and development and how an understanding of schools as places can be used to increase children’s enjoyment of school.